A dynamic framework for evaluating tax policies in Taiwan: an application of optimal control theory - Lin, San-Li, author; Fan, Chuen mei, advisor; Kling, Robert, committee member; Loomis, John B., committee member; Mushinski, David, committee member (Colorado State University. Libraries, 2006)
In order to eliminate or alleviate the problem of "double taxation" on dividends, the government in Taiwan introduced in 1998 a new tax system with the intent to integrate corporate and personal income taxes. However, some problems, such as the impacts on tax revenues, capital accumulation, and income distribution, may still emerge in this new tax system in the future. In the presence of heterogeneous income groups with different rates of time preference, industries of different degrees of incorporation with adjustment costs, and government deficits, this study builds a dynamic general equilibrium model to provide a more comprehensive framework capable of capturing a realistic dynamic environment in Taiwan, based on the optimal control theory. This study also displays the concept of net cash flows in accounting, applies it to the model, and sets the objective of industries to pursue the maximization of their net cash flows in the dynamic general equilibrium tax model. By applying transversality conditions to each sector, this study derives the solution for the theoretical model to ensure that all the equilibrium conditions are satisfied. Then, this study designs several tax policy scenarios, focusing on the corporate income tax integration plans, to theoretically explore how to apply simulation schemes to the model, to attempt to theoretically investigate the possible effects of these policies on the structure of the model and equilibrium values, and further to check if simulation results are consistent with equilibrium conditions. In this theoretical model, what we can obtain are the aggregated results for each sector, not the disaggregated ones which can only be done by an empirical study. Therefore, it would be expected that the framework of this study can be used as a blueprint to examine the performance of the new tax system after 1998 if more disaggregated information becomes available in the future, and further evaluate whether the objectives of tax integration are accomplished.
Keywords: finance; models; studies; households